The pecularities of formation and development of event marketing strategies - Navickas, Valentinas; Malakauskaitė, Asta (Business: Theory and Practice, 2007)
The necessity determined by the global economy – it is the ability to transform the flows of ideas into technological and commercial success. This process includes not only the creation of new products and services, but also the introduction of new methods to stimulate and promote sales. Creativity and innovativeness tend to become the most important competencies that enable companies to gain and retain competitive advantage. The study shows that event marketing and other interactive forms of communication have developed as the answer to the challenges of mass-adaptation era. They ensure the direct dialogue between a company and its clients; they enable a company to modify its message according to the expectations of its target market. Moreover, new interactive marketing tools improve the image and perception of a company and stimulate the volume of sales.Article in Lithuanian.Įvykio rinkodaros strategijų formavimosi ir plėtros ypatumaiSantrauka. Globalios ekonomikos suformuota būtinybė – sugebėjimas idėjų srautus transformuoti į technologinę ir komercinę įmonės sėkmę. Šį procesą sudaro ne tik naujų prekių bei paslaugų kūrimas, bet ir naujų pardavimo skatinimo būdų paieška. Kūrybiškumas, inovatyvumas tampa esmine kompetencija, kuri gali padėti įmonei įgyti ir išlaikyti konkurencinį pranašumą. Tyrimas parodė, kad įvykio rinkodara ir kitos interaktyvios komunikacijos priemonės susiformavo kaip atsakas į masinio pritaikymo eros iššūkius, kadangi jos užtikrina tiesioginį įmonės ir jos klientų dialogą, suteikia galimybę modifikuoti siunčiamą žinutę pagal tikslinės grupės vartotojų lūkesčius, tobulina prekės ženklo įvaizdį ir jo suvokimą, stimuliuoja prekybos apimtis.Reikšminiai žodžiai: interaktyvi rinkodara, interaktyvios rinkodaros priemonės, įvykis, įvykio rinkodara, įvykio rinkodaros strategijos, paramos strategija.